Política fiscal e seus efeitos no desenvolvimento regional do Estado da Bahia: um estudo sobre os incentivos fiscais no Estado da Bahia no período de 1994 a 2005 - Pinto, Elisia Medeiros (2006)
The investment attraction policy that has been adopted by each state member of Brazil for the last years has raised a competition that is known by fiscal war that gets harder now-a-days.The process formation of brazilian federalism, emphasizes the economical change, that stopped being agro-exporter and becoming industrial was a part or a try to understand the centralization of power by the government better, which remains the creation and encashment of taxes, and the destination of what was gained with them. In this federalist scenario, that in a determined historical period, survived with an emptyness in the government leadership, the states would have more autonomy in giving fiscal and financial incentive, using its main tax the ICMS. The main objective of this research, which is the base of this text, was to make an analysis of fiscal and financial aids given between 1994 and 2004 by Bahia´s government, and from it, check, if, the used policy helped gain the expect results in direct and indirect employment and in the development of the region. Summarizing, it was tried to investigate if, effectively, there was any kind of increase in the economical activities in the state of Bahia, and consequently, a higher participation of its GNP in Brazil s GNP. From the results, it was clear that the policy that was adopted by Bahia s government, without the federal government coordination, and so, without being inserted in a macroeconomic scale, was posite in relation to the state s economic growth, showing an increase of over 35% of the GNP, 11% above the nation s GNP, considering the same period. So, when analyzing the socioeconomic indicators of the state, in which more than half of the state s population survive under poverty levels, it s possible to testify that these policies didn t achieve the desired effects to achieve the economic and social development, needing to be rewatched and improved.